English Instructors’ Leadership Styles (The Sample of Dokuz Eylul University) - Güçer, Halil; Denkci Akkaş, Ferdane (International Journal of Scientific Research and Management (IJSRM), 2017)
Today, since teachers, students as well as parents are included in the process of leadership, school principals are not considered the sole leaders any longer. Distributed leadership which requires the involvement of various people in school leadership has paved the way for teacher leadership which is defined as “having effective teaching leadership within the classroom, playing leadership roles out of the classroom, becoming a role model both for the students and colleagues in terms of education and school development processes, working cooperatively with them, influencing them and contributing to the transformation of the school community in terms of the school targets that will improve the school according to the needs of the modern time. The purpose of this study is to determine the English instructors’ teacher leadership style in terms of McGregor’s X and Y Theory and to reveal whether their teacher leadership style varies according to such personal and professional factors as their gender and teaching experience. The data were collected from 80English instructors employed at Dokuz Eylul University, School of Foreign Languages in Izmir, Turkey via“ Teacher Leadership Styles Scale” developed by Deniz and Hasançebioğlu (2003). The data were analysed with SPSS 22 packet program and the results have revealed that the instructors have a semi-democratic leadership style although they tend to be autocratic as well.